What happens at the lesson start?. Issue 1 (2nd January 2016) - Saloviita, Timo
Abstract: Transitional periods, such as lesson starts, are necessary steps from one activity to another, but they also compete with time for actual learning. The aim of the present study was to replicate a previous pilot study on lesson starts and explore possible disturbances. In total, 130 lesson starts in Finnish basic education in grades 1–9 were studied using systematic observation performed by 79 preservice teachers. The results corresponded with a previous pilot study indicating that lesson starts were generally orderly and teachers used effective means to manage events. However, lessons started 5 min late on average. Male teachers were evaluated to have better classroom order than female teachers. Small effects were observed based on the gender of the student and the hour of the lesson. No association was found between disturbances in the classroom and the grade level, group size or presence of a classroom assistant.